1985
DOI: 10.1073/pnas.82.20.6922
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of leukotriene release by macrophages ingesting Toxoplasma gondii.

Abstract: Mouse resident peritoneal macrophages incubated with ionophore A23187 or opsonized zymosan released leukotrienes (LT) B4 and C4 (LTB4 and LTC4) and LTC4 and LTD4, respectively. In contrast, incubation with Toxoplasma gondii, an obligate intracellular protozoan, led to the formation of 11-, 12-, and 15-hydroxyicosatetraenoic acids (HETEs), together with an unidentified compound, designated compound X. Each of these compounds incorporated [3H]arachidonic acid from the macrophage during phagocytosis of T. gondi. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
(31 reference statements)
2
16
0
Order By: Relevance
“…Our data indicates that peripheral blood monocytes respond to C. albicans challenge by releasing AA. Prior studies have demonstrated that mononuclear cells release AA in response to a variety of microorganisms including Fusobacterium nucleatum, Gardnerella vaginalis, Peptostreptococcus anaerobius, Histoplasma capsulatum, Mycobacterium intercellulare, Leishmania donovani, and Toxoplasma gondii [39][40][41][42][43]. Additional investigations in our laboratory have similarly indicated that C. albicans also induces alteration in eicosanoid metabolism in alveolar tissue macrophages.…”
Section: -Glucan Laminariheptaosesupporting
confidence: 61%
“…Our data indicates that peripheral blood monocytes respond to C. albicans challenge by releasing AA. Prior studies have demonstrated that mononuclear cells release AA in response to a variety of microorganisms including Fusobacterium nucleatum, Gardnerella vaginalis, Peptostreptococcus anaerobius, Histoplasma capsulatum, Mycobacterium intercellulare, Leishmania donovani, and Toxoplasma gondii [39][40][41][42][43]. Additional investigations in our laboratory have similarly indicated that C. albicans also induces alteration in eicosanoid metabolism in alveolar tissue macrophages.…”
Section: -Glucan Laminariheptaosesupporting
confidence: 61%
“…These data are consistent with earlier in vitro reports which indicated that the exposure of macrophages to T. gondii triggers an increase in arachidonic acid release and lipoxygenase activity that largely favors the 12/15-LOX product 12(S)-HETE (37). However, since 12(S)-HETE is the major product of murine 12/15-LOX (24,52), it is possible that the apparently selective nature of the 12/15-LOX-dependent increased 12(S)-HETE production in wild-type mice may be related to the sensitivity of our assay. Also, the increased abundance of this 12/15-LOX product could represent a decrease in metabolism/uptake or an increased proportion of 12/15-LOX-expressing cells rather than an induction of expression or activity in a given cell type.…”
Section: Resultsmentioning
confidence: 83%
“…Some reports demonstrated that murine res ident macrophages generate LTB4 when stimulated with A23187 (16)(17)(18) or endotoxin (19), while the metabolites in macrophages are differentially altered by endotoxin tolerance (19) and Listeria immunization (20), suggest ing that macrophages collected from an in flammatory site may have different natures from resident macrophages.…”
Section: Discussionmentioning
confidence: 99%